Answer:
30 degrees.
Step-by-step explanation:
Rotational symmetry is defined as a figure having the same appearance when rotated by a certain angle.
The wheel has 12 "handles." We can use these as reference points when rotating the image.
We also know that we can rotate by a total of 360 degrees. We can say that:
360/12 = 30 degrees.
Each time you rotate the wheel by 30 degrees, the image will end up on another handle (looks the same). This shows rotational symmetry.
I hope this helps!
Easiest way is if you substitute each point (x,y) into each set of equations and both points work for both equations in the system of equations, then it is the correct answer
Otherwise substitute one equation for y in the other equation:
2x + 6 = x^2 + 5x + 6
-2x - 6. -2x -6
0 = x^2 + 3x. Factor
0 = x (x + 3)
Solve: x = 0. x + 3 = 0. ——> x = -3. Substitute into one original equation to get y value for
y = 2x + 6.
y = 2(0) + 6. y = 2(-3) + 6
y = 6. y = -6 + 6 —-> y = 0
(0 , 6) And. (-3 , 0)
Answer:
Step-by-step explanation:
c
Answer:
![x\leq 76](https://tex.z-dn.net/?f=x%5Cleq%2076)
Step-by-step explanation:
Let x = unknown number
![\implies \dfrac89 \times (x-4)\leq 64](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac89%20%5Ctimes%20%28x-4%29%5Cleq%2064)
![\implies \dfrac{8(x-4)}{9}\leq 64](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B8%28x-4%29%7D%7B9%7D%5Cleq%2064)
Multiply both sides by 9:
![\implies 8(x-4)\leq 576](https://tex.z-dn.net/?f=%5Cimplies%208%28x-4%29%5Cleq%20576)
Expand brackets:
![\implies 8x-32\leq 576](https://tex.z-dn.net/?f=%5Cimplies%208x-32%5Cleq%20576)
Add 32 to both sides:
![\implies 8x\leq 608](https://tex.z-dn.net/?f=%5Cimplies%208x%5Cleq%20608)
Divide both sides by 8:
![\implies x\leq 76](https://tex.z-dn.net/?f=%5Cimplies%20x%5Cleq%2076)
Answer:
There are infinite solutions that solve the system
Step-by-step explanation:
- The solution can be expressed as
(there are infinite solutions that solve the system). This results from rearranging terms in the first or second equation.
- This is because the first equation is a linear combination of the second one (this is, the first equation equals (-1) times the second equation). This means that the second equation does not add any information about x and y: it says exactly the same as the first equation about the relationship between x and y.
- Then, in terms of solving the system, you have one unique expression (not repeated) that shows the relationship between y and x. This means that, any pair of (x,y) that meet the requirements expressed by
, will solve the system. Then we have infinite solutions.